2019
DOI: 10.7759/cureus.6456
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Hemorrhage Outcomes by Intrapartum Risk Stratification at a Single Tertiary Care Center

Abstract: Open Access Original Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 11 publications
(17 reference statements)
3
14
0
Order By: Relevance
“…Previous studies that examined OBH risk assessment tools have showed significantly higher sensitives of the tools in predicting OBH and OBH-T in patients categorized as high risk. [8][9][10][11][12] This is consistent with our study, which has comparable accuracy data, including PPV and likelihood ratios. In a recent review of OBH risk assessment tools completed by Ende and Butwick, 13 the PPV ranges for OBH (defined as 1,000 mL of blood loss or greater) and OBH-T were 9-11 and 1-23, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies that examined OBH risk assessment tools have showed significantly higher sensitives of the tools in predicting OBH and OBH-T in patients categorized as high risk. [8][9][10][11][12] This is consistent with our study, which has comparable accuracy data, including PPV and likelihood ratios. In a recent review of OBH risk assessment tools completed by Ende and Butwick, 13 the PPV ranges for OBH (defined as 1,000 mL of blood loss or greater) and OBH-T were 9-11 and 1-23, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, previous validation studies have not examined this population and hospital setting. [8][9][10][11][12] It is important to recognize the complexity in collecting race and ethnicity data; however, it is also worthwhile to express that this data increases our data collection on groups traditionally excluded or aggregated into larger population groups. 20 Secondly, by incorporating accuracy data in statistical analysis, both pre-and post-inclusion of intrapartum risk factors, this study allows for more robust data with regards to the possible efficacy of identifying high-risk patients with repeated risk assessment after labor floor admission.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is comparable to other studies such as Ruppel et al and Hussain et al, who respectively noted that 48 and 43% of hemorrhages occurred in women categorized as low risk. 9 13 This firmly supports the need for hemorrhage risk assessment tool improvement. Clinicians should execute caution and have persistent clinical vigilance even with a score of low risk using a hemorrhage risk prediction tool and ensure utilization of all aspects of an OBH safety bundle.…”
Section: Discussionsupporting
confidence: 53%
“…While risk factors are well-documented from descriptive studies (i.e. longer second stage labor, infant macrosomia, oxytocin administration during labor); an estimated 40% of PPH occurs during births without these commonly-noted risk factors [ 8 , 19 , 61 64 ] as assessed with available screening tools. A reason for this inaccuracy in risk assessment is due to the fact that PPH is a diagnosis only made after a high cumulative blood loss has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…statistics listed Table Left denotes GG participants and increased positive correlation between greater oxytocin administration and higher blood loss. Right denotes AG/AA participants (larger red circles = AA) and a diminished effect of greater exposure to intrapartum oxytocin on eventual total blood loss labor); an estimated 40% of PPH occurs during births without these commonly-noted risk factors [8,19,[61][62][63][64] as assessed with available screening tools. A reason for this inaccuracy in risk assessment is due to the fact that PPH is a diagnosis only made after a high cumulative blood loss has occurred.…”
Section: Discussionmentioning
confidence: 99%